2020
DOI: 10.1148/rycan.2020200011
|View full text |Cite
|
Sign up to set email alerts
|

Utility of T2-weighted MRI to Differentiate Adrenal Metastases from Lipid-Poor Adrenal Adenomas

Abstract: Materials and Methods: With institutional review board approval, this study retrospectively compared 40 consecutive patients (mean age, 66 years 6 10 [standard deviation]) with metastases to 23 patients (mean age, 60 years 6 15) with lipid-poor adenomas at 1.5and 3-T MRI between June 2016 and March 2019. A blinded radiologist measured T2-weighted signal intensity (SI) ratio (SI nodule / SI psoas muscle), T2-weighted histogram features, and chemical shift SI index. Two blinded radiologists (radiologist 1 and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Lesions that lost signal intensity on opposed-phase images compared with inphase images and demonstrated hypo-or isointensity to the liver on T1-images and iso-or slight hyperintensity to the liver on T2-images were diagnosed as adenomas. 7,10 Confirmation of the diagnosis of adenoma was made by calculating the signal intensity index calculated (>16.5%) [(signal intensity on in-phase imaging − signal intensity on opposed-phase imaging)/(signal intensity on in-phase imaging)] × 100%. 40 Patients without signal intensity loss on MRI (n = 5) underwent additional washout CT, resulting in the diagnosis of adrenal adenoma.…”
Section: Main Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions that lost signal intensity on opposed-phase images compared with inphase images and demonstrated hypo-or isointensity to the liver on T1-images and iso-or slight hyperintensity to the liver on T2-images were diagnosed as adenomas. 7,10 Confirmation of the diagnosis of adenoma was made by calculating the signal intensity index calculated (>16.5%) [(signal intensity on in-phase imaging − signal intensity on opposed-phase imaging)/(signal intensity on in-phase imaging)] × 100%. 40 Patients without signal intensity loss on MRI (n = 5) underwent additional washout CT, resulting in the diagnosis of adrenal adenoma.…”
Section: Main Pointsmentioning
confidence: 99%
“…is limited because they may also show washout in the adenoma range. 7 A previous study by Tu et al 10 showed promising results for distinguishing adrenal metastases from benign lipid-poor adenomas using T2-weighted MRI and logistic regression models combining T2-weighted signal intensity and T2-weighted heterogeneity.…”
mentioning
confidence: 99%
“…In general, computed tomography (CT) is better than magnetic resonance imaging (MRI) for lesion assessment. This kind of examination not only overcomes the influence of respiratory motion artefacts and obtains high-quality images but also has the advantages of a fast scanning speed and a low price (12,13). On the basis of conventional CT, dual-energy spectral detector CT (SDCT) provides more parameters that can be used to evaluate lesions, which can be used for better evaluation of adrenal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…When using CT, tumor heterogeneity and size have been found to be consistently useful features between malignant and benign adrenal masses. For instance, previous reports from Ho et al, [ 39 ] Tu et al, [ 40 , 42 ] and Schieda et al [ 43 ] found that malignant adrenal tumors were larger and more heterogeneous than benign ones. In our study, large masses (mean diameter of the lesion >4 cm) and heterogeneous lesions (obvious necrosis) were excluded; therefore, LD and SD showed no significant differences between L-PAA and ASSM.…”
Section: Discussionmentioning
confidence: 99%